Determinan Produk Domestik Regional Bruto Provinsi Riau: Analisis Deret Waktu - Gharin, Marlev A (Jurnalku, 2024)
Riau Province is the largest center of palm oil industry in Indonesia, with Crude Palm Oil (CPO) production contributing approximately 19 to 22 percent to the national output during the period of 2017-2021. The processing industry and the agricultural sector have managed to shift the dominance of the mining sector, contributing 28.08 and 26.83 percent, respectively, to the Regional Gross Domestic Product (PDRB) of Riau in the year 2021. This research aims to investigate the influence of the number of palm oil mills (PKS), plantation area (LUAS), and production quantity (PROD) on the Regional Gross Domestic Product (PDRB) of Riau Province. These factors were analyzed using time series data from 2008 to 2021, employing the STATA 17 application with multiple linear regression methods. Based on the regression analysis results, it was found that only the LUAS variable has a significant positive impact, while the PKS and PROD variables have a non-significant negative impact on the GDP, with slope coefficients of -0.034 for the PKS variable, 1.285 for the LUAS variable, and -0.04 for the PROD variable. However, the government is expected to optimize the value-added in processing and plantation production industries to have a positive impact on the improvement of the local economy. Provinsi Riau merupakan sentra industri kelapa sawit terbesar di Indonesia dengan produksi Crude Palm Oil (CPO) berkisar antara 19 hingga 22 persen kontribusi nasional selama periode 2017-2021. Industri pengolahan dan sektor pertanian mampu menggeser dominasi sektor pertambangan dengan kontribusi mencapai 28,08 dan 26,83 persen terhadap Produk Domestik Regional Bruto (PDRB) Riau Tahun 2021. Penelitian ini bertujuan untuk menyelidiki pengaruh jumlah pabrik kelapa sawit (PKS), luas perkebunan (LUAS), dan jumlah produksi (PROD) terhadap Produk Domestik Regional Bruto (PDRB) Provinsi Riau. Faktor-faktor tersebut dianalisis menggunakan data time series periode 2008-2021 menggunakan aplikasi STATA 17 dengan metode regresi linear berganda. Berdasarkan hasil analisis regresi, ditemukan bahwa hanya variabel LUAS yang berpengaruh signifikan positif sedangkan variabel PKS dan PROD berpengaruh tidak signifikan negatif terhadap PDRB dengan koefisien kemiringan sebesar -0,034 untuk variabel PKS, sebesar 1,285 untuk variabel LUAS, dan sebesar -0,04 untuk variabel PROD. Untuk itu, Pemerintah diharapkan untuk melakukan optimalisasi nilai tambah pada industri pengolahan dan produksi perkebunan agar dapat berdampak pada peningkatan perekonomian daerah.